Tight intra-operative blood pressure control versus standard care for patients undergoing hip fracture repair - Hip Fracture Intervention Study for Prevention of Hypotension (HIP-HOP) trial: study protocol for a randomised controlled trial - Moppett, Iain K.; White, Stuart; Griffiths, Richard; Buggy, Donal (BioMed Central, 2017)
Background: Hypotension during anaesthesia for hip fracture surgery is common. Recent data suggest that there is an association between the lowest intra-operative blood pressure and mortality, even when adjusted for co-morbidities. This is consistent with data derived from the wider surgical population, where magnitude and duration of hypotension are associated with mortality and peri-operative complications. However, there are no trial to data to support more aggressive blood pressure control. Methods/design: We are conducting a three-centre, randomised, double-blinded pilot study in three hospitals in the United Kingdom. The sample size will be 75 patients (25 from each centre). Randomisation will be done using computer-generated concealed tables. Both participants and investigators will be blinded to group allocation. Participants will be aged >70 years, cognitively intact (Abbreviated Mental Test Score 7 or greater), able to give informed consent and admitted directly through the emergency department with a fractured neck of the femur requiring operative repair. Patients randomised to tight blood pressure control or avoidance of intra-operative hypotension will receive active treatment as required to maintain both of the following: systolic arterial blood pressure >80% of baseline pre-operative value and mean arterial pressure >75 mmHg throughout. All participants will receive standard hospital care, including spinal or general anaesthesia, at the discretion of the clinical team. The primary outcome is a composite of the presence or absence of defined cardiovascular, renal and delirium morbidity within 7 days of surgery (myocardial injury, stroke, acute kidney injury, delirium). Secondary endpoints will include the defined individual morbidities, mortality, early mobility and discharge to usual residence. Discussion: This is a small-scale pilot study investigating the feasibility of a trial of tight intra-operative blood pressure control in a frail elderly patient group with known high morbidity and mortality. Positive findings will provide the basis for a larger-scale study.